The Non-Orthodox in The Martyrdom of John the New by Gregory Camblak Patterns of Dehumanization - Wolski, Jan Mikołaj (Studia Ceranea, 2021)
The image of the non-Orthodox in Camblak’s work is unequivocally negative. Behind the abusive rhetoric lie patterns well known to social psychology. One can easily recognize the author’s dehumanizing attitude, which reveals the meaning of many elements of Camblak’s narrative in The Martyrdom of John the New. The concept of dehumanization is useful for the study of the attitude of medieval literate elites towards minorities. Although at its core it concerns cognitive phenomena it immediately makes us think about their behavioral implications.